2009
DOI: 10.1007/s00464-008-0318-x
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic surgery (SILS) for totally extraperitoneal (TEP) inguinal hernia repair: first case

Abstract: To the Editors There has been an open debate in the most recent literature on possible progress in laparoscopic surgery, aiming mainly at benefits of minimization of surgical trauma and improvement of cosmesis. Natural-orifice transluminal endoscopic surgery (NOTES) and single-incision laparoscopic surgery (SILS) have emerged as approaches whose advantages and possible applications are being explored and tested currently.Operations eligible for NOTES approach are determined by the availability of entry point o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 9 publications
0
92
0
Order By: Relevance
“…On further scrutiny, 16 articles 15,19,22,[35][36][37][38][39][40][41][42][43][44][45][46][47] were used in our literature review and 3 studies comparing LESS TEP with LAP TEP were found to have useful data for the summative outcome. One study commented on a previous report.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On further scrutiny, 16 articles 15,19,22,[35][36][37][38][39][40][41][42][43][44][45][46][47] were used in our literature review and 3 studies comparing LESS TEP with LAP TEP were found to have useful data for the summative outcome. One study commented on a previous report.…”
Section: Resultsmentioning
confidence: 99%
“…One study commented on a previous report. 37 Three studies 22,40,45 compared LESS TEP with LAP TEP and were combined to produce a summative outcome. A flow chart of the literature search according to PRISMA guidelines 48 is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Many procedures such as (2,(10)(11)(12)(13)(14). The fi rst SILS practice in the world has been performed in our clinic (7).…”
Section: Discussionmentioning
confidence: 99%
“…Single-incision laparoscopic surgery (SILS) has now been adopted for appendectomy, cholecystectomy, and inguinal hernia repair. [6][7][8] Additionally, recent studies have demonstrated successful results of gastric or colorectal surgery using the SILS approach. 9,10) In contrast, only a few studies of single-incision thoracoscopic surgery (SITS) have been reported.…”
Section: Introductionmentioning
confidence: 99%